Environmental Impact Analysis and Land Use Disputes By Lhoong Setia Mining (Ltd.) in Lhoong District, Aceh Besar Regency - Muhajir; Syahrizal; Muhammmad Jamil; Zakaria; Hatta, Muhammad (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The iron ore mining activities conducted by PT. Lhoong Setia Mining (LSM) in Lhoong District, Aceh Besar, have caused significant environmental damage and triggered land use conflicts between the company and the local community. From 2011 to 2013, the mining operations polluted the Krueng Sob River, degraded ecosystems, and destroyed the livelihoods of local fishermen. Furthermore, the company left behind un-reclaimed mining pits, worsening environmental degradation. The company’s failure to comply with reclamation obligations as mandated by Article 39 of Law No. 3 of 2020 constitutes a violation of environmental responsibility principles. The local community, which was inadequately involved in decision-making, suffered both economic and ecological harm. A land conflict arose due to the company's control over 500 hectares without fair community consent. Legal resolution may be pursued through litigation or non-litigation mechanisms, such as mediation or civil lawsuits based on unlawful acts.